Language and linguistics within the paradigm space (Język(i) w czasie i przestrzeni, 2021)
The article discusses the function of paradigms (as introduced by Kuhn) for researching language and linguistics, concentrating on the issue of relevance of paradigms for linguistic research, the competition of paradigms and their mutual relations. The author postulates the existence of three possible paradigms in the study of language: the formal paradigm (where language is considered to be a formal object, as in some strands of Structuralism, and early work by Chomsky), the mentalist paradigm (language as an instrument of thought, Chomsky’s more recent theories), and the communicative paradigm (language as an instrument of communication, various pragmatically oriented approaches, and also discourse studies).